LAS CORPORACIONES DE RADIOTELEVISIÓN PÚBLICA DE LA UNIÓN EUROPEA Y EL INCIPIENTE USO DE LA WEB 2.0 PARA COMUNICAR RSC - Tania FERNÁNDEZ LOMBAO, (Fonseca, Journal of Communication, 2023)
Corporate Social Responsibility is a concept that defines the model of corporate governance based on responsible, horizontal and interactive accountability as opposed to closed and rail control systems. This type of management has been associated, at an initial moment, with private enterprise in the context of globalization, although gradually being implemented in the public, and consequently in the state-owned broadcasting corporations of the European Union.